PENERAPAN MODEL PEMBELAJARAN KOOPORATIF TIPE THINK PAIR SHARE TERHADAP HASIL BELAJAR ARITMATIKA SOSIAL DI KELAS VII SMP NEGERI 1 MOTOLING BARAT - Gebi Bone; Ontang Manurung; Marvel Grace Maukar (Universitas PGRI Sumatera Barat, 2026)
This study aims to determine the effect of the cooperative learning model of the Think Pair Share (TPS) type on mathematics learning outcomes of grade VII students of SMP Negeri 1 Motoling Barat. This study employed a quasi-experimental method with a pretest-posttest control group design. The research subjects consisted of class VII-A (N=20) as the experimental group and class VII-B (N=17) as the control group, selected through purposive sampling based on academic ability equivalence. The experimental class was taught using the TPS cooperative learning model, while the control class used conventional learning. Descriptive analysis showed that the average posttest score of the experimental class (79.75) was significantly higher than the control class (46.50). Based on the independent t-test, tcount= 13.23 > ttable = 2.03 at significance level 0.05. Therefore, H₀ is rejected and H₁ is accepted, indicating that student mathematics learning outcomes taught with the TPS cooperative learning model are significantly better than those taught through conventional learning.